Divorce commentator : What it is.. And adapted Method and legal - ساجدة طه محمود (College of Education for Women, 2019)
Banned temporarily divers has increased greatly in the society and for silly reasons. This issue aroused a great controversy .There are so many motivations to Aleve deep in it. There are so many approach hes to talk it . It deserves to be studied in a simple way but thoroughly and comprehensively .Dune to this great importees and to its spread among married couples for their agnorance concerning its voles' and dangers . I have been stimulated and encouraged to go through and close read its details aleomplish this research. It is a olevided in to an introduction and three chapters : 1-chapter one : defines the terminology of banned temporarily clearer's and it legal situation . 2-chapter two : Terms of banned temporarily devoirs, its results and devisions . 3-chapter three : Religions and legal position of banned temporarily devours . Then the conclusion where results and recommendations are set clearly.